Identification of two Monilia species from apricot in China - Liang-fen YIN; Ming-li CAI; Sheng-fang DU; Chao-xi LUO (Journal of Integrative Agriculture)
Monilinia fructicola, Monilia mumecola and Monilia yunnanensis have been reported as the causal agents of brown rot disease on stone fruits in China. Up to date, these species have been identified from peach and plum, and M. mumecola has also been reported on apricot recently. To investigate whether M. fructicola and M. yunnanensis can cause brown rot disease on apricot in China, 37 isolates were collected from four orchards in Chongqing and Beijing municipalities in 2014. These isolates were divided into two phenotypes according to their distinct colony appearances. Two representative isolates of each phenotype and reference species of M. mumecola from apricot were selected for further analysis. Based on the morphological characterization and molecular identification, the two phenotypes of isolates were identified as M. fructicola and M. yunnanensis, respectively.